The Employment Effects of a Wage Subsidy for the Young during an Economic Recovery - Astrid Kunze; Marta Palczyńska; Iga Magda (Institute of Labor Economics (IZA), 2023)
This study investigates the employment effects of a large-scale wage subsidy programme for the young unemployed that was introduced in 2016, during a period of recovery in the Polish economy. The focus is on the question of whether the effects differed between men and women. The study employs a large population administrative data set from the unemployment register, and exploits for identification the fact that firms were only eligible to participate in the wage subsidy programme if the newly recruited worker was below age 30 and was previously unemployed. A challenge in this research is that before 2016, standard packages of active labour market programmes for all unemployed and specific programmes for unemployed below age 30 had been in place. Exploiting the long period and broad data coverage, we estimate the differential impact of the new programme using a difference-in-discontinuities design. The main finding is that over the medium term, the new wage subsidy programme was effective for low- and middle-skilled eligible young women, but not for men. We discuss the policy implications of such programmes targeting young unemployed people.
Keywords: J08; J64; J68; 330; wage subsidy; youth unemployment; gender differences; difference-in-discontinuities; register data